The future of sterling - Day, A. C. L. (Oxford : Clarendon Press, 1954)
The purpose of this study is to ask questions that should be of interest both to practical policy-makers and to theoretical economist, and to provide tentative answers to some of them concerning the problems of sterling.
Bibliography p. [228]
usc 07/11/18
Loans
Keywords: Sterling area